Increasing Teacher Competence In The Industrial Revolution Industri 4.0 - Okpatrioka, Okpatrioka; Sopian, Sopian (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
In the era of the industrial revolution 4.0, new technologies emerged which resulted in extraordinary changes in all fields, including education. If the teacher's function is only limited to transferring knowledge to students or just teaching in the classroom, then its role will be replaced by technology in this 4.0 industrial revolution era. As agents of change, teachers are required to have pedagogical competence, professional competence, personality competence, and social competence. In the era of industrial revolution 4.0, teachers must be proactive in taking advantage of the changes in science and technology that are currently happening.Technology will make teachers more confident and easier to teach their students so they can turn classrooms into creative, innovative and fun learning spaces. This paper aims to reveal the role of teachers in the era of education 4.0. The method used is literature study with descriptive analysis techniques. The results of the study show that (1) The current problem of education in Indonesia is the low quality of education compared to other countries, (2) Teacher competence (3) Education 4.0 is the answer to the era of the industrial revolution 4.0 in the world of education.